The Influence of Product Innovation and Service Quality to Buying Decision and the Impact to Repeat Buying at Progo Road Bandung - Siahaan, Rianty Agustina; Lahindah, Laura; Merisa, Merisa (The Asian Journal of Technology Management (AJTM), 2018)
Abstract. The growth of culinary industry has encourage the entrepreneur to create more innovative product and excellent service that will affect customers buying decision and create customer engagement to repeat buying. Progo Road, one the culinary clustering in Bandung city have an attractive growth at the last year. Many housing now change to culinary industry and grow faster. Most of them have a very innovative product and serving customer well. The purpose of this research is to analyze the influence of product innovation and the service quality to buying purchasing decision and the impact to repeat buying. Survey conducted in the culinary industry along the Progo Road. This research is associative research using SEM-PLS. Samples taken as many as 384 people who come to Progo Road. By Using WarpPLS 3.0, this research found that product innovation and the service quality influence buying decision in the culinary industry along the Progo Road, but did not give an impact to repeat buying.Keywords:Â  Buying decision, culinary industry, product innovation, repeat buying, service quality.Â